A COMPARATIVE STUDY OF ISSUES FACED BY HEALTHCARE PROFESSIONALS IN THE TREATMENT OF INDIVIDUALS WITH SUBSTANCE USE DISORDERS IN PAKISTAN (The Research of Medical Science Review, 2025)
Healthcare providers must have an extensive understanding of the unique cultural and regional variations in order to effectively treat substance use disorders. This study aimed to assess and compare the difficulties encountered by medical practitioners in treating substance use disorders across different provinces in Pakistan. The sample consisted of 32 healthcare experts (8 from each province) working in different Govt. and private Drug Rehabilitation centers and hospitals (psychiatric units) from Punjab, Sindh, Baluchistan and Islamabad who were working in the field of drug addiction. As data collection tool, Focused group discussions were carried from the experts from each province. A qualitative research design was employed and thematic analysis was used to extract the findings in the form of initial themes, sub themes and major themes. The challenges experienced by healthcare professionals varied widely as revealed by thematic analysis ranging from the use of substance, myths about using drugs to the age group in each of the four provinces. Three primary themes emerged: Socio-Cultural Differences, Treatment Related Differences, and Policy & Governance Differences. By highlighting the unique issues faced in different regions of Pakistan, this study not only emphasized the necessity for indigenous traditions and interventions but also modifications in existing policies. These results of this study were manifolds as it enhanced the understanding of indigenous challenges faced by health care professionals in major provinces of Pakistan in cultural specific context and also will help in tailoring the indigenous cultural needs specific interventions to treat the adults with substance used disorders in Pakistan by training medical practitioners to tackle the unique challenges involved in the treatment of substance use disorders.